Women’s Empowerment Metric for National Statistical Systems (WEMNS): Development and psychometric assessment of a face-to-face survey module - Kathryn M. Yount; Agnes Quisumbing; Ruth Meinzen-Dick; Hazel Malapit; Md. Zahidul Hassan; Shelton S. E. Kanyanda; Sudhindra Sharma; Md. Imrul Hassan; Jessica Heckert; Flor Paz; Pankaj Pokhrel; Wilbert D. Vundru; et al. (PLoS ONE, 2026)
Data to monitor progress towards gender-related Sustainable Development Goals (SDGs) remain limited. A comprehensive, concise set of metrics is needed for routine national data collection to monitor progress toward these goals. Our team developed and tested the Women’s Empowerment Metric for National Statistical Systems (WEMNS) survey module for use by national statistical offices and survey organizations in low- and middle-income countries (LMICs) to measure women’s and men’s empowerment. This paper summarizes the process of developing the WEMNS module and presents detailed results of a psychometric assessment of face-to-face surveys in Bangladesh, Malawi, and Nepal. Exploratory factor analysis and confirmatory factor analysis (CFA) in the pooled sample confirmed that most of the 13 item sets had adequately identified factor structures aligned with specific empowerment constructs and gender-related SDGs. In multi-group CFA assessing measurement equivalence of item sets across gender and countries, configural invariance was observed for 9 of 13 item sets across genders and across country settings. At least partial scalar invariance was observed for one item set across genders and no item sets across country settings. Spearman pairwise correlations among WEMNS factor scores derived from final CFA models showed weak associations, suggesting item sets were weakly related and distinct. Overall, Spearman pairwise correlations of 13 WEMNS-derived factor scores with external measures for basic needs, resources, agency, and subjective well-being were weak, but five moderately high correlations were conceptually aligned. In sum, the WEMNS measures require refinement and further psychometric assessment to confirm their use to make valid comparisons of empowerment across country settings and gender.